STRATEGI PENGEMBANGAN WISATA PANTAI BANDENG DI DESA KAYUWATU, KECAMATAN KAKAS KABUPATEN MINAHASA - Intan Livia Assa; Bet El S. Lagarense; Aldy Adrianus Tatali (UPT Penelitian Sekolah Tinggi Ilmu Pariwisata Manado, 2022)
The tourist area of Milkfish Beach has its own charm from the beaches in Minahasa with white, soft and smooth sandy beach. However, this beach is not taken care with proper attention. The facilities are damaged and need reparations. The research aims to propose a development strategy for Milkfish Beach tourist attraction. The research was conducted by identifying and analyzing the ways on how to manage and develop the Milkfish Beach tourist attraction in Kayuwatu Village. This study uses a combination of qualitative and quantitative descriptive research methods. The data sources are primary data including the physical condition of the land, facilities and infrastructure as well as secondary data which includes population, location and topographic maps. Methods of data collection is done through field research, documentation, interviews and observation. Based on the results of the study, it was concluded that the Bandeng Beach tourism area really needs reparation and development of damaged facilities. The design is done in order to make Milkfish Beach much better and more beautiful to look at and visit so that it can attract more tourists to visit Milkfish Beach. This will hopefully increase income for the community and local government especially in the tourism sector.